TAMAN KELINCI SEBAGAI WAHANA REKREASI DAN EDUKASI DENGAN PENERAPAN ARSITEKTUR BERKELANJUTAN DI KARANGANYAR - Dindha Nirmalasari; Hadi Setyawan; Bambang Triratma (ARSITEKTURA, 2016)
Rabbits are classified as a mammal in the order Lagomorpha. Rabbit offers various potentials and benefits yet still unnoticeable by many. As cosmopolitan animal, the mammal adapts easily into wide range of habitats. Karanganyar is an example where one may find rabbits’ rearing and breeding industries. At the moment, such industries limit their operation to merely provide the demands of rabbits meat. Moreover, Directorate of Livestock and Animal Health of Karanganyar states rabbit farmers in the area (specifically Tawangmangu) once underwent livestock failure.Karanganyar Government plans to create several leisure- and education-based tourist attractions to diversify its tourism industry, which in turn directly contribute to people’s welfare. Based on the notion, a Taman Kelinci is proposed as a way to harness rabbits’ potentials. Its plan and design utilise sustainable architecture methodology since it fits the purpose of symbiotical relations between the environmental, economical, social, and cultural matters; the realisation of the design will benefit the people economically without neglecting other aspects stated beforehand. The Taman Kelinci is an effort to explore rabbits’ potentials  as well as to attract and benefit people – which covers four issues that is education, leisure, conservation, and marketing.  Keywords: Education, Leisure, Rabbit, Sustainable Architecture.